GAMBARAN KELAINAN REFRAKSI PADA SISWA-SISWI DI SEKOLAH DASAR NEGERI 55 BANDA ACEH - Fauziah Hayati; Eva Mardalena (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2021)
This study is entitled â€œDescription of Refraction Disorder to Students in Public Elementary School 55 Banda Aceh Year 2015â€. Vision disorder is an important health problem, especially to child, considering 80% of information during first 12 months child life was obtained through a vision. The refraction disorder of child if not overcome in early so it will cause amblyopia. The amblyopia is incurable automatically, and if not treated it will cause a permanent vision disorder. As for the problem in this study was how the description of disorder refraction of students of public basic school 55 of Banda Aceh. By the purpose to find out the frequency distribution of refraction disorder according to gender of students of public elementary school 55 Banda Aceh. This research method is desrciptive with cross sectional approach. Results of study the students of Public Elementary School 55 of Banda Aceh were dominant have a normal vision sharp (emmetropia). Of research results indicated who have myopia is found 31%. Respondent with class VI level were more have myopia refraction disorder if compared to other class levels. Based on investigations that has been conducted of 60 samples was not found who have hypermetropia disorder.Keywords: Disorder of refraction, child